Lacosamide-induced sinus node dysfunction followed by severe agranulocytosis - Makoto Shibata; Reona Hoshino; Chisato Shimizu; Masayuki Sato; Natsumi Furuta; Yoshio Ikeda (BMC Neurology, 2021)
Abstract Background Lacosamide (LCM) is the antiepileptic drug approved by the U.S. Food and Drug Administration in 2008 that facilitates slow activation of the voltage-gated sodium channels. Neutropenia and cardiac events including sinus node dysfunction (SND) and atrioventricular block have been previously reported as adverse effects of LCM. To date, there have been no reports of severe agranulocytosis resulting in death associated with LCM. Additionally, there have been no reports of concomitant SND and agranulocytosis after LCM administration. Herein we report the first case of LCM-induced severe SND followed by agranulocytosis. Case presentation The patient with focal epilepsy was initiated on LCM 100 mg/day and the dose was increased to 200 mg/day on the 9th hospital day. Severe SND developed on the 10th hospital day and LCM was discontinued. Thereafter agranulocytosis appeared on the 11th hospital day, and the patient died from septic shock on the 15th hospital day. Conclusions This case illustrates the need for careful follow-up of the electrocardiogram and the complete blood cell counts when initiating LCM. Moreover, it should be noticed that various side effects may occur simultaneously in the early period of LCM use, even for a short time and at low dosages.